2019
DOI: 10.1002/jcb.28616
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of silibinin in cell behavior during osteogenic phenotype

Abstract: Natural molecules, such as flavonoid, are very welcome strategies to modulate bone turnover. This prompted us to comprehend better the effect of silibinin on osteoblast metabolism, mainly considering intracellular pathways able to drive cell adhesion to differentiation. By exploring in vitro approaches, our data show a modulatory effect of the silibinin (200 μg/mL) on the osteoblast intracellular signaling, contributing with decisive pathways governing cell adhesion, differentiation, and further mineralization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Sr 2+ could promote the adhesion and proliferation of cells on biomaterials [ 60 ]. Cytoskeleton rearrangement is required to drive morphological changes in cells during adhesion and differentiation processes, as well as to guide the release of calcification vesicles into the ECM [ 61 ]. Importantly, Src has also been related to governing ECM remodeling by somehow contributing to matrix metalloproteinase (MMP) involvement in response to biomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…Sr 2+ could promote the adhesion and proliferation of cells on biomaterials [ 60 ]. Cytoskeleton rearrangement is required to drive morphological changes in cells during adhesion and differentiation processes, as well as to guide the release of calcification vesicles into the ECM [ 61 ]. Importantly, Src has also been related to governing ECM remodeling by somehow contributing to matrix metalloproteinase (MMP) involvement in response to biomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…In human chondrocytes in vitro, SB was demonstrated to inhibit the expression of IL-1β-induced inflammatory markers, including COX-2, iNOS, NF-κB, NO, PGE2, TNF-α and IL-6 [68]. Similarly, SB (0.42 mM) regulated intracellular signalling to reprogram the inflammatory response in osteoblast SB [69]. In summary, SB was shown to be protective against osteoarthritis (OA) through inhibiting the inflammatory response and cartilage matrix degradation in vitro (in human OA chondrocytes) and in vivo (in mice OA models).…”
Section: Skin and Bone Cellsmentioning
confidence: 94%
“…In addition, either the effect or mechanism of silybin or silibinin on OA subchondral bone destruction has not been fully explored. However, studies on different osteoblasts reported that the active component of silymarin, silybin, has effects on adhesion, proliferation, and differentiation processes of mice osteoblast (Fernandes et al, 2019), another study reported that silybin increases the mRNA expression of COL‐1, ALP, OCN, BMP‐2, and RUNX2 thereby improving osteogenic differentiation of human BMSCs (Ying et al, 2013). Therefore, the effect of silymarin‐associated components on OA subchondral bone destruction is worthy of study.…”
Section: Methodsmentioning
confidence: 99%
“…Improves osteogenic differentiation of BMSCs (Fernandes et al, 2019;Ying et al, 2013) Abbreviations: ADAMTS, a disintegrin and metalloproteinase with thrombospondin motifs; COX, cyclooxygenase; ECM, extracellular matrix; ER, endoplasmic reticulum; IL-1, interleukin-1; MDA, malondialdehyde; MMP, matrix metalloproteinase; NAIP, natural anti-inflammatory product; PARP, poly ADP-ribose polymerase; ROS, reactive oxygen species; TNF-α, tumor necrosis factor-α.…”
Section: Icariinmentioning
confidence: 99%